2019
DOI: 10.1101/653873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutrophils promote CXCR3-dependent itch in the development of atopic dermatitis

Abstract: These authors contributed equally and order determined by coin toss. Abstract 1Chronic itch remains a highly prevalent disorder with limited treatment options. Most chronic itch 2 diseases are thought to be driven by both the nervous and immune systems, but the 3 fundamental molecular and cellular interactions that trigger the development of itch and the 4 acute-to-chronic itch transition remain unknown. Here, we show that skin-infiltrating neutrophils 5are key initiators of itch in atopic dermatitis, the most… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 115 publications
2
40
0
2
Order By: Relevance
“…Thus, we undertook a chemogenetic gainof-function approach to demonstrate that selective activation of basophils alone is sufficient to induce itch in mice. Although basophils critically promote AD-like skin inflammation (Imai et al, 2019;Kim et al, 2014a;Walsh et al, 2019), surprisingly, we found that they do not mediate chronic spontaneous itch. Furthermore, our study reveals that while mast cells and histamine are critical for acute itch in the steady state, basophils and LTC4 mediate acute itch flares in AD-like disease.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, we undertook a chemogenetic gainof-function approach to demonstrate that selective activation of basophils alone is sufficient to induce itch in mice. Although basophils critically promote AD-like skin inflammation (Imai et al, 2019;Kim et al, 2014a;Walsh et al, 2019), surprisingly, we found that they do not mediate chronic spontaneous itch. Furthermore, our study reveals that while mast cells and histamine are critical for acute itch in the steady state, basophils and LTC4 mediate acute itch flares in AD-like disease.…”
Section: Discussionmentioning
confidence: 55%
“…IL-24 acts as an activator of STAT3, which is also activated by IL-31 to promote elongation of the nerve fibers, followed by enhanced itching [63]. Additionally, IL-24 upregulated the expression of CXCL1 [54], a chemokine that can evoke itch through multiple pathways [64,65]. These data suggest the involvement of IL-24 in the mechanism of pruritus in AD.…”
Section: Il-24 and Itchmentioning
confidence: 83%
“…Eosinophils were recruited early following MI skin exposure ( Fig 1F ) and are known regulators of allergic disease and tissue remodeling [ 41 ]. We also saw MI-driven accumulation of neutrophils in the skin ( Fig 1G ); these cells are associated with psoriasis and atopic dermatitis [ 42 , 43 ]. To our knowledge, eosinophils and neutrophils have not been studied in vulvodynia or in MI contact allergy but may have important modulatory roles in both.…”
Section: Discussionmentioning
confidence: 99%